1986
DOI: 10.1093/clinchem/32.2.329
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of total bilirubin by use of bilirubin oxidase.

Abstract: We used an enzymatic method for measuring total bilirubin in serum. Results by this method varied linearly with bilirubin concentrations to at least 300 mg/L. The day-to-day precision (CV) of the method ranged from less than 1% to about 11% at bilirubin concentrations of 183 and 12 mg/L, respectively. Commonly used anticoagulants, serum preparation materials, and selected drugs had no effect on the apparent bilirubin concentration, but turbidity caused a slight increase and hemoglobin concentrations of 2 g/L r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 0 publications
0
12
1
Order By: Relevance
“…Parenteral alimentation with lipids is normally provided as nutrition to preterm infants or sickly newborns 19 . Although the bilirubin oxidase method is affected by the presence of serum hemoglobin and lipid emulsion 11 , we found in this study that hemolysate or serum containing emulsion did not affect unconjugated bilirubin measurement by the UnaG method. Additional studies are required to determine whether the various drugs used in clinical neonatal medicine interfere with UnaG-based detection.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Parenteral alimentation with lipids is normally provided as nutrition to preterm infants or sickly newborns 19 . Although the bilirubin oxidase method is affected by the presence of serum hemoglobin and lipid emulsion 11 , we found in this study that hemolysate or serum containing emulsion did not affect unconjugated bilirubin measurement by the UnaG method. Additional studies are required to determine whether the various drugs used in clinical neonatal medicine interfere with UnaG-based detection.…”
Section: Discussioncontrasting
confidence: 52%
“…A major disadvantage of these conventional methods is to produce an inaccurate result in serum samples with turbidity. For example, the bilirubin oxidase method measures bilirubin levels by monitoring a change in absorbance at 450 nm, which is affected by turbidity due to hemoglobin or lipid emulsion 11 . High-performance liquid chromatography is the only method for directly measuring unconjugated bilirubin 12 , but is impractical for routine clinical use.…”
mentioning
confidence: 99%
“…Total bilirubin concentrations were determined enzymatically using the bilirubin oxidase method 17 . Preliminary studies in our laboratory showed that results obtained using this assay correlated strongly ( n = 10 bile samples, r = 0.997) with those obtained using the Jendrassik–Grof diazo method of measurement of bilirubin concentrations, which has been reported to be less susceptible to interference by photobilirubin 18 …”
Section: Bile Physical Chemistrymentioning
confidence: 93%
“…21,22 Oxidation of both conjugated and unconjugated bilirubin to biliverdin by either bilirubin oxidase or horse-radish peroxidase and hydrogen peroxide and the subsequent oxidation of biliverdin to a pale Diazonegative polar pigment cause characteristic absorption peaks of bilirubin to disappear. [23][24][25] Broderson and Bartels noted that albumin inhibits the oxidation, suggesting that dissociation of bilirubin from albumin or other carrier proteins could facilitate its oxidation. 23 Low pH as well as several compounds that binds to proteins promotes the displacement of bilirubin from albumin.…”
Section: Discussionmentioning
confidence: 99%